2021
DOI: 10.1021/acs.jctc.1c00826
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Quantum Interference in Photochemical Reactions

Abstract: Interferences emerge when multiple pathways coexist together, leading toward the same result. Here, we report a theoretical study for a reaction scheme that leads to constructive quantum interference in a photoassociation (PA) reaction of a 87Rb Bose–Einstein condensate where the reactant spin state is prepared in a coherent superposition of multiple bare spin states. This is achieved by changing the reactive scattering channel in the PA reaction. As the origin of coherent control comes from the spin part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This article focuses on achieving the ground state of Kagome lattices using a variational quantum eigensolver (VQE). Such quantum simulations, variational and otherwise, have become quite popular in recent years and been performed for a variety of other systems using diverse methodologies. However, even constructing the ground state of a single plaquette within the Kagome lattice requires 12 qubits. Various studies , have demonstrated that when attempting to attain the ground state of Hamiltonians with a significant number of qubits (>8), any Hamiltonian-agnostic ansatz, beyond a certain depth, inevitably leads to a barren plateau.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on achieving the ground state of Kagome lattices using a variational quantum eigensolver (VQE). Such quantum simulations, variational and otherwise, have become quite popular in recent years and been performed for a variety of other systems using diverse methodologies. However, even constructing the ground state of a single plaquette within the Kagome lattice requires 12 qubits. Various studies , have demonstrated that when attempting to attain the ground state of Hamiltonians with a significant number of qubits (>8), any Hamiltonian-agnostic ansatz, beyond a certain depth, inevitably leads to a barren plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, molecular scattering experiments, particularly those conducted under cold and ultracold conditions, yield unparalleled insights into intermolecular interactions. A comprehensive understanding of the quantum dynamics in ultracold environments has the potential to reveal innovative strategies, possibly employing quantum phenomena such as superposition, entanglement, and interference patterns to control reaction outcomes. …”
mentioning
confidence: 99%
“…Coherence, often manifested through interference, has been observed in photoionization ( 1 ) and in inelastic and reactive scatterings involving light species such as hydrogen deuteride (HD), hydrogen fluoride (HF), and deuterium (D 2 ) in molecular beam experiments ( 2 5 ), in which comparison with full quantum-scattering calculations is needed to identify the signatures of interference. Coherence can also be leveraged to control the product-state distribution through interference between reaction pathways ( 6 , 7 ). Early experimental success has been shown in light-induced processes, such as photoassociation ( 8 ), photoionization ( 9 ), and photodissociation ( 10 , 11 ).…”
mentioning
confidence: 99%